1999
DOI: 10.2486/indhealth.37.174
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Job Stress and Health in Japan: Review of Current Evidence and Future Direction.

Abstract: Abstract:With the increasing concern about job stress, there is a growing body of literature addressing psychosocial job stress and its adverse effects on health in Japan. This paper reviews research findings over the past 15 years concerning the assessment of job stress, the relationship of job stress to mental and physical health, and the effects of worksite stress reduction activities in Japan. Although studies were conducted in the past using ad-hoc job stress questionnaires, wellestablished job stressor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
3
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(124 citation statements)
references
References 80 publications
9
107
3
5
Order By: Relevance
“…Job strain has been shown to be associated with fewer leisure-time physical activities in previous studies in Japan. 20,21 However, using the same sample, we previously reported fewer leisure-time physical activities both in high-class occupations and low-class occupations. 5 This apparent discrepancy may be attributable to other work-related factors, such as greater job commitment among managers.…”
Section: Other Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Job strain has been shown to be associated with fewer leisure-time physical activities in previous studies in Japan. 20,21 However, using the same sample, we previously reported fewer leisure-time physical activities both in high-class occupations and low-class occupations. 5 This apparent discrepancy may be attributable to other work-related factors, such as greater job commitment among managers.…”
Section: Other Covariatesmentioning
confidence: 99%
“…22,23 Females are frequently employed in support roles. 20 Furthermore, they are assumed to have more job mobility than men in Japan because they bear a larger share of childcare responsibilities that men do and might have to change or give up jobs as a result. Women in low-skill occupations may feel that their positions are often unstable.…”
Section: Other Covariatesmentioning
confidence: 99%
“…This is consistent with previous studies conducted at Occupational Medicine (Oxford), 45 where the journal's most highly cited article of all time 107 was only 5 years old. A similar situation was also demonstrated at Industrial Health, 103 where the most highly cited article 108 was only 8 years old. Such findings in EOH need to be seen in context, however, as history has shown that very few articles ever get cited at high rates.…”
Section: Discussionmentioning
confidence: 64%
“…In 1992, the United Nations reported occupational stress as the illness of 20 th century and after that world health organization reported it as an epidemic problem in the world [5]. Also, in a study done by Kawakami in 1999 occupational stressors were reported to be the strongest cause of psychological damages especially depression [6]. Some systematic researches reported that working women are healthier (physiologically or psychologically) than housewives [7][8][9][10][11][12][13], but in some other studies no significant statistical differences in satisfaction with marriage and family life or anxiety level between working and nonworking women was found [14,15].…”
Section: Introductionmentioning
confidence: 99%